PERBANDINGAN LAJU ALIR SALIVA LANSIA PENDERITA DIABETES MILETUS PENGGUNA DAN BUKAN PENGGUNA GIGI TIRUAN LEPASAN - Siti Rusdiana Puspa Dewi; Sri Wahyuningsih Rais; Mayang Pramudya Sari (Odonto : Dental Journal, 2019)
Introduction: Older people are often proportional to the loss of teeth and reduced some body functions, such as decreased salivary flow rate. Systemic diseases such as diabetes that are common in the elderly lead to the decrease of salivary production. The use of denture is reported to increase the salivary flow rate.Methods: This study was an analytic survey with purposive sampling design involving 40 elderly people with diabetes mellitus with age range 45-59 years. Samples divided into two groups, group 1 was using removable denture, while group 2 was not using removable denture. Unstimulated saliva was collected by spitting method for 5 min. Salivary flow rate is obtained by measuring saliva volume in ml/min. Data were analyzed using unpaired t-test with significance level p<0.05.Results: The results showed that elderly people with diabetes mellitus using removable denture had higher salivary flow rate than not using removable denture significantly.Conclusion: the use of removable denture in elderly diabetic people is able to increase the salivary flow rate.